The Effect of Soursop Leaf Extract in Reducing Pain in Gout Arthritis - Dimas Hadi Prayoga; Wimar Anugrah (STIKes Patria Husada Blitar, 2023)
Gout arthritis is a disease characterized by pain caused by deposits of monosodium crystals that accumulate in the joints due to high levels of uric acid in the blood. Currently, pain management treatment for gout arthritis patients focuses on pharmacological treatment by providing analgesics to relieve pain. Soursop leaf extract has been proven to have an effect in reducing pain, but there has been no research regarding the effect of boiled soursop leaves to reduce it. The aim of this study was to analyze the effect of giving soursop leaf decoction on reducing pain in gout arthritis patients. The research used a quasi-experimental design with a one group pre-posttest design. The sample selected by using purposive sampling technique, totaling 18 people. The independent variable was soursop leaf decoction. The dependent variable was the pain in gout arthritis. The data analysis used the Wilcoxon Signed Ranks Test statistical test. The compounds contained in soursop leaves function as a strong analgesic (pain reliever) and have antioxidant properties. The antioxidant properties contained in soursop leaves can reduce the formation of uric acid by inhibiting the production of the enzyme xanthine oxidase. This combination of analgesic and anti-inflammatory properties can reduce gout. This study found that there was an effect of giving soursop leaf decoction on reducing pain in gout arthritis patients.